2020
DOI: 10.1111/fcp.12559
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of alliin and allicin on apoptosis and senescence in luminal A and triple‐negative breast cancer: Caspase, ΔΨm, and pro‐apoptotic gene involvement

Abstract: Breast cancer is the most frequent cancer in women worldwide, and drug resistance is common in all breast cancer types. The combination of natural products with chemotherapies has attracted attention, as it was found that natural compounds enhance the effects of standard cancer chemotherapeutic drugs and protect from side effects. Into the different natural products, garlic has been recognized for its antitumor properties. It is suggested that its anticancer effects are associated with its organo‐sulfur compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The antitumoral effect of garlic induced by its bioactive sulfur compounds like allicin, diallyl-sulfides (DAS), diallyl-disulfides (DADS), and diallyl-trisulfides (DATS), raises interest for many studies [ 11 , 12 , 13 ]. DATS can stimulate cytotoxicity by targeting reactive oxygen species (ROS) and can activate the ROS dependent caspase pathway, therefore it can promote apoptosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antitumoral effect of garlic induced by its bioactive sulfur compounds like allicin, diallyl-sulfides (DAS), diallyl-disulfides (DADS), and diallyl-trisulfides (DATS), raises interest for many studies [ 11 , 12 , 13 ]. DATS can stimulate cytotoxicity by targeting reactive oxygen species (ROS) and can activate the ROS dependent caspase pathway, therefore it can promote apoptosis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, allicin reduced cell viability and induced apoptosis by triggering the loss of ΔΨm, caspase-3, caspase-8, and caspase-9 activation, downregulation of BCL-XL expression as well as upregulation of NOXA, BAK, and P21. On the other hand, alliin endorsed clonogenicity, induced senescence, and did not demonstrate pro-apoptotic effects in breast cancer cells [129]. Allicin also suppressed proliferation and induced glioma cell apoptosis in vitro by intrinsic mitochondrial and extrinsic Fas/FasL mediated pathways [130].…”
Section: Organosulfur Compoundsmentioning
confidence: 97%
“…An investigation indicated that allicin (45) induces apoptosis in breast cancer cells (MCF-7 and HCC-70) mediated by CASP3, CASP8 and CASP9 activation and loss of mitochondrial membrane potential (∆Ψm). These pro-apoptotic pathways (intrinsic and extrinsic) are also accompanied by upregulation of CDKN1A/p21 , PMAIP1/NOXA and BAK1 expression, as well as downregulation of BCL2L1 [ 339 ].…”
Section: Natural Compounds and Cancermentioning
confidence: 99%